Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1973
DOI: 10.3382/ps.0520799
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Rous Sarcomas in Two Lines of Chickens ,

Abstract: A genetic difference between two lines of chickens in the incidence of regression of Rous sarcomas was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1976
1976
1999
1999

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Inhibition was significantly less when the cells were obtained from chickens with progressively growing wing web tumors or from uninoculated controls. We have previously shown that the incidence of regression of Rous sarcomas is significantly influenced by the particular line of chickens (Cotter et al, 1973a), the presence of thymus tissue (Cotter et al, 1976), and the host age at inoculation (Cotter et al, 1973b). The data suggest that tumor regression in chickens is mediated by a delayed type hypersensitivity reaction in which thymus dependent cells (T cells) become sensitized to and subsequently effect the destruction of tumor cells.…”
Section: Discussionmentioning
confidence: 96%
“…Inhibition was significantly less when the cells were obtained from chickens with progressively growing wing web tumors or from uninoculated controls. We have previously shown that the incidence of regression of Rous sarcomas is significantly influenced by the particular line of chickens (Cotter et al, 1973a), the presence of thymus tissue (Cotter et al, 1976), and the host age at inoculation (Cotter et al, 1973b). The data suggest that tumor regression in chickens is mediated by a delayed type hypersensitivity reaction in which thymus dependent cells (T cells) become sensitized to and subsequently effect the destruction of tumor cells.…”
Section: Discussionmentioning
confidence: 96%
“…of a 10" 3 dilution of the stock virus. Tumors usually appeared on the ninth or tenth day post-inoculation (PI) and were subjectively scored for size according to the procedure of Cotter et al (1973). A progressor was a chicken bearing a tumor either increasing, or plateaued, in size by 70 days PI whereas a regressor was a host whose tumor clearly was decreasing in size or had disappeared completely in the same time period.…”
Section: Chickensmentioning
confidence: 99%
“…Rous sarcoma regression was studied by Cotter et al (1973) in an inbred line of White Leghorns and a non-inbred line of New Hampshires, each of which was genetically susceptible to RSV. The frequency of spontaneous tumor regression in the inbred Leghorns exceeded 50% and in the New Hampshires was approximately 5%, the difference between lines being statistically significant.…”
Section: Introductionmentioning
confidence: 99%
“…In chickens, Rous sarcomas may regress spontaneously (Stenkvist and Ponten, 1963), but the incidence of tumor regression was influenced significantly by strain (Cotter et al, 1973), genetic selection (Gyles and Brown, 1971;Carte et ah, 1972), and by the major histocompatibility complex (Collins et al, 1977;Schiermznetal, 1977).…”
Section: Introductionmentioning
confidence: 97%